Formula Romance dalam Novel City Lite: Empat Bulan Yang Lalu Karya Kincirmainan - Ubab, Gus (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2024)
This research aims to describe the Romance Formula in the Novel “Empat Bulan Yang Lalu” by Kincirmainan, part of the City Lite series. This research uses a qualitative descriptive method with a popular fiction approach based on Cawelti's theory supported by Radway's romance formula. Data were collected through reduction, display, and conclusion drawing techniques, then analyzed descriptively. Based on the results of the study and discussion, it was found that the novel City Lite: Empat Bulan yang Lalu uses one typology pattern of narrative structure, namely the Pamela pattern. This pattern is used in the novel to describe complicated romance and free relationships, which are influenced by the past. This novel follows several sequences of the romance formula proposed by Radway, providing an overview of how this formula is applied in the context of the story. Abstrak Penelitian ini bertujuan untuk mendeskripsikan formula romance dalam novel